Reduced graphene oxide on screen-printed carbon electrodes as biosensor for Escherichia coli O157:H7 detection - Barthasarathy, Piravin Raj; Wan Salim, Wan Wardatul Amani (MDPI, 2020)
Rapid development and deployment of biosensors for pathogen quantification is needed for flood-stricken areas. Drinking-water supplies in flooded areas become a disease threat owing to mixture with sewage discharge. In such exigent conditions, water is filtered through a microfiltration technique that is moderately effective in removing bacteria and non-effective in removing viruses. Quantification of pathogens using biochemical techniques does not provide real-time data and requires transportation of water samples to laboratories for analysis. However, transportation services are severely affected during flooding, and hence on-site testing may be the only option. WHO specifies that diagnostic devices are to be made ASSURED – affordable, sensitive, specific, user-friendly, rapid and robust, equipment-free, and deliverable to end-users. To fulfil ASSURED criteria, we developed a low-cost electrochemical biosensor integrated with an Arduino® microprocessor encased in a portable platform for E. coli O157:H7 quantification. The working electrode (WE) of a screen-printed carbon electrode (SPCE) was modified with reduced graphene oxide (rGO). Rabbit serum IgG, a non-specific antibody towards E. coli O157:H7, was immobilized on the WE. We tested the specificity of E. coli O157:H7 binding to IgG/rGO/SPCEs and rGO/SPCEs at 4 to 4 × 108 CFU/ml. We chose a potential range of -0.35 to 0.07 in LSV to compare the current values at different concentrations. At -0.14V, IgG/rGO/SPCEs distinguished E. coli concentrations of 4 and 4 × 108 CFU/ml with current value of 17 µA and 1 µA, respectively. However, the IgG/rGO/SPCE does not distinguish between E. coli concentration of 4 × 107 and 4 × 108 CFU/ml. The rGO/SPCE does not distinguish E. coli concentration of 4 and 4 × 108 CFU/ml, as evidenced by almost similar current values in both concentrations. This study indicates the potential of non-specific antibodies for E. coli O157:H7 quantification during water-quality monitoring in flooded areas.